Systematic identification and characterization of high efficiency Cas9 guide RNAs for therapeutic targeting of ADAR - Benjamin G. Gowen; Kory Melton; Weng In Leong; Prachi Khekare; Shannon McCawley; Jean Chan; Pierre Boivin; Vihasi Jani; Aaron J. Cantor; Akshay Tambe; Mary Haak-Frendscho; Mary J. Janatpour; et al. (PLoS ONE, 2025)
Therapeutic targeting of the adenosine deaminase ADAR has great potential in cancer and other indications; however, it remains unclear what approach can enable effective and selective therapeutic inhibition. Herein, we conduct multi-staged guide RNA screening and identify high efficiency Cas9 guide RNAs to enable a CRISPR/Cas-based approach for ADAR knockout. Through characterization in human primary immune cell systems we observe similar activity with two-part guide RNA and single guide RNA, dose responsive activity, similar guide activity rank order across different cell types, and favorable computational off-target profiles of candidate guide RNAs. We determine that knockout of ADAR using these guide RNAs induces pharmacodynamic responses primarily consisting of immunological responses such as a type I interferon response, consistent with the known function of ADAR as a key regulator of dsRNA sensing. We observe similar biological effects with targeting only the p150 isoform or both p110 and p150 isoforms of ADAR, indicating that at least in the contexts evaluated, loss of p150 ADAR mediates the primary response. These findings provide a resource of well-characterized, high efficiency ADAR-targeting Cas9 guide RNAs suitable for genomic medicines utilizing different delivery modalities and addressing different therapeutic areas.